Prediction of shunt dependent hydrocephalus following aneurysmal subarachnoid hemorrhage “algorithm based management” - Shrestha, Shikher; Bishokarma, Suresh; Lohani, Subash; Sapkota, Suresh; Thapa, Sangita; Gongal, Dinesh Nath (Nepal Journal of Neuroscience, 2018)
Aneurysmal subarachnoid hemorrhage (aSAH) is a devastating disease with a high rate of mortality and permanent morbidity. An important neurologic complication is hydrocephalus reported to range from 6 to 67% while only 10-20% of them will require permanent CSF diversion. The purpose of this study was to identify predictive factors for the development of shunt dependant hydrocephalus among patients with aSAH. This is a retrospective study conducted in among 72 patients who underwent clipping of aneurysm for subarachnoid hemorrhage in our institute during 2 years. EVD placement done for acute hydrocephalus while VP shunt was done for chronic hydrocephalus or requiring prolonged EVD placement. Various clinical and radiological factors were registered on admission and during the intensive care stay. Multivariate logistic regression analysis was done to predict risk of shunt dependant hydrocephalus. P value less than 0.05 was considered significant. Among 72 patients with aSAH. Intraventricular extension of blood was seen in 24 (33.3%) patients while hydrocephalus was seen among 19 (26.4%) patients. Eight patients (11.1%) required EVD placement for acute hydrocephalus while 10 (13.9%) patients required permanent shunt placement for chronic hydrocephalus. In univariate analysis, SAH with fisher grade >2, presence of hydrocephalus, intraventricular extension of hemorrhage and need of EVD placement were found to have significant association in shunt dependency. However multivariate logistic regression model showed EVD requirement for acute hydrocephalus as an independent predictor of shunt dependent hydrocephalus at p value 0.006 (OR=21.3; 95% CI=2.38 to 191.51). Hydrocephalus is a common complication following aneurysmal subarachnoid hemorrhage. SAH with fisher grade >2, presence of hydrocephalus, intraventricular extension of hemorrhage and need of EVD placement were found to have significant association in shunt dependency however only EVD requirement is an independent predictor of SDH